10 + 6(-9 + -4x) = 10(x + -12) + 8
10 + (-9 * 6 + -4x * 6) = 10(x + -12) + 8
10 + (-54 + -24x) = 10(x + -12) + 8
Combine like terms: 10 + -54 = -44
-44 + -24x = 10(x + -12) + 8
Reorder the terms:
-44 + -24x = 10(-12 + x) + 8
-44 + -24x = (-12 * 10 + x * 10) + 8
-44 + -24x = (-120 + 10x) + 8
Reorder the terms:
-44 + -24x = -120 + 8 + 10x
Combine like terms: -120 + 8 = -112
-44 + -24x = -112 + 10x
Solving
-44 + -24x = -112 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
-44 + -24x + -10x = -112 + 10x + -10x
Combine like terms: -24x + -10x = -34x
-44 + -34x = -112 + 10x + -10x
Combine like terms: 10x + -10x = 0
-44 + -34x = -112 + 0
-44 + -34x = -112
Add '44' to each side of the equation.
-44 + 44 + -34x = -112 + 44
Combine like terms: -44 + 44 = 0
0 + -34x = -112 + 44
-34x = -112 + 44
Combine like terms: -112 + 44 = -68
-34x = -68
Divide each side by '-34'.
x = 2
Simplifying
x = 2